Continuity Of Care In Midwifery For Mrs. S With The Application Of Effleurage Massage During Third Trimester Pregnancy - Puji Lestari, Diah; Fuadah, Samrotul; Suryaningsih, Suryaningsih; Rahma Dini, Putri (Devotion : Journal of Research and Community Service, 2026)
Introduction Continuity of Care (COC) Midwifery Care or continuous midwifery care is a concept that emphasizes the provision of continuous and integrated health care, which aims to provide optimal health services to patients by building strong and sustainable relationships between patients and health service providers. (1) Research objective : To carry out Continuity of Care Midwifery Care on Mrs. S at PMB Adibah Fitriana, S.Tr.Keb, Bdn with Varney's 7-step thinking and documentation with SOAP. Research methods : This research study uses a case study. The research subject in this study is Mrs. S G1P0A0. Data Collection Time : conducted from April to December 2025 Results : During pregnancy, Mrs. S complained of back pain, during labor, Mrs. S complained of cramps and bloody mucus coming out of the birth canal, during the postpartum period, the mother stated that her breast milk came out a little, Mrs. S's baby was fussy at night and had difficulty sleeping. The interventions that have been given are giving efflurage massage in the third trimester of pregnancy, assisting with childbirth with 60 steps of APN, doing oxytocin massage for postpartum mothers, giving massage therapy to fussy babies, the birth control used by Mrs. S is an implant birth control. Conclusion: After efflurage massage therapy was carried out for a duration of 5-10 minutes, Mrs. S 's back pain complaints decreased.